The impact of emotional intelligence and intercultural competence on work productivity of volunteers in respect to age and length in volunteering - Ingrida Vinickyte; Rita Bendaravičienė; Jolita Vveinhardt (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
The aim of this study is to evaluate the impact of emotional intelligence and intercultural competence on the effectiveness of volunteer work with respect to the age and length of volunteering. 174 volunteers who have volunteered or are volunteering under the Erasmus + European Voluntary Service participated in the survey. The results of the study are presented as answers to the following problematic questions: Does higher emotional intelligence and higher intercultural competence increase the effectiveness of volunteer work? Does intercultural competence increase due to higher emotional intelligence? Do older volunteers have higher intercultural competence and higher emotional intelligence? Do volunteers with greater volunteering experience have higher intercultural competence and emotional intelligence? Do people with longer volunteering experience at the European Voluntary Service (EVS) have a higher level of intercultural competence and emotional intelligence? Based on the results of the study, factors that have a significant impact on the productivity of internationally active volunteers were identified.
Keywords: M12; M14; M19; 650; volunteer; volunteering; emotional intelligence; intercultural competence; work productivity